(3GdeMGhQI GdUdGMjI aj GdeMGLGI GdGUWdGMjIs - (3Ydj Hf eMeO Hf YHO GdYRjR Hf aJhM GdKYdHj GdTGaYqj, JGL GdOjf, GdeYQha H` GHf GdOQjge hH` GHf CHj GdNjQ,J (B762 (3g` s
(3ChdgG (B:s
(3hHYO, adeG cGfJ GdCMGLj eeG JfHg GdNGWQ, hJdbM GdacQ hJegQ aj GddZI MUd eMGhQI Hjfj hHjf GdaGVd UdGM GdOjf GdUaOj s
(3BNQgG (B:s
(3bO MRJ aj PQhI eLO eQJbi haRJ jG bhJ GdbdhH HGdoJbi ddoOQ hGdjGbhJ daXc GfJbi s
(3HChdgG Jedc eDQN HSfI (B984(3g````s
(3HgG bGFeI HCSeGA eUfaGJ GdeDda GHf GdOQjges
(3fSNI NRGFfjI s
(3gh eLehY GdeMGhQGJ GdeJHGOdI Hjf GdeDda hUdGM GdOjf GdUaOj GdeJhai (B764 (3g``` s
(3ajgG VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs